Estimation of length of endotracheal tube insertion by foot length in newborns - Hannan, Nabeela; ., Prema; H. S., Surabhi (International Journal of Contemporary Pediatrics, 2018)
Background: Intubation is a common procedure for neonates. This study was designed to determine whether the foot length (FL) can predict the depth of endotracheal (ET) tube insertion in newborns. Methods: This one year prospective cross-sectional study was done on 50 neonates admitted to NICU under the Department of Paediatrics, Rajarajeswari Medical College and Hospital, Bangalore from January 2016 to June 2017. The FL was measured and compared with the optimal depth of ET tube insertion. The data was analysed using SPSS version 20.0. Results: The mean FL was 7.42±0.75cms and mean optimal ET tube length was 7.70±0.71cm. The correlation between optimal ET tube length and foot length was noted in 70% of the babies and significant strong positive correlation was noted between optimal ET tube length and FL (r=0.780; p<0.001; R2=0.607). Significant differences were noted in mean FL and mean optimal depth of ET tube in term newborns (p=0.013) and those with normal weight (p=0.016). Conclusions: Foot length could be used as a simple and easy predictor in the estimation of endotracheal tube length in newborns.